Factors Associated with Compliance to Treatment Adherence of HIV/AIDS Patients in Kendari City - Muhammad Sabil, La Ode; Tasnim, Tasnim; Asri, Andi; Hariadhin Depu, Anry (Magister Kesehatan Universitas Mandala Waluya, 2024)
Introduction: HIV/AIDS remains a serious problem both in Indonesia as a whole and specifically in Southeast Sulawesi. The primary way to address HIV/AIDS is through treatment. Numerous factors make it challenging to predict the causes of compliance and non-compliance among HIV/AIDS patients in seeking treatment. Therefore, research is needed to develop interventions aimed at improving treatment compliance among HIV/AIDS patients. This study aims to analyze factors related to the behavior of treatment compliance among HIV/AIDS patients in the city of Kendari, Southeast Sulawesi Province. Method: This research is a quantitative study with an analytical research design. The method used is a Cross-Sectional Study. The sample size of 88 individuals. Data collection was conducted through a questionnaire technique. Descriptive analysis was performed using frequency distribution tables, while inferential analysis utilized the Chi-square test and/or Fisher's Exact Test. Results: The research findings indicate that only 2 factors (perception of disease severity and health worker attitudes) are related to treatment compliance, while the other 6 factors (perceived benefits of treatment, perceived barriers to treatment, family support, health counselor support, drug availability, and health education) show no association and have no detected connection. The most dominance factor is the healthcare worker attitude. Conclusion : The conclusion of this research is that perception of diseases severity and healthcare worker attitude is the 2 variabel that have connection with treatment adherence and need improvement to keep the patient and improve their treatment.